The Treatise on Reason by al-ʿAllāmah Muḥammad Bāqir ibn Ḥusayn Khān al-Balakī: Study, Verification, and Commentary - Masoud Muhammad Ali, (Islamic Sciences Journal, 2025)
The Treatise on Reason undertakes a scholarly study of the theory of knowledge among the theologians and philosophers, especially ancient Greek philosophy and Islamic Illuminationist philosophy, and it sets forth issues related to reason: Among them: an explanation of the meaning of reason, which is a luminous entity used by the animal spirit for sensation, by the outward human soul for perception and knowledge, and by the inner soul — that is, the spirit stripped of matter — for gnosis, according to the capacities of each of them. And it affirms the middle view regarding the role of reason between the Sophists and the materialists, and its relationship with the senses in completing the process of knowledge. Among them: the directing of the causes of knowledge between unity and multiplicity, through interpreting the saying of the theologians: “the reference of all perceptions is reason,” and interpreting the well-known statement that the causes of knowledge are three — the senses, report, and reason — though they are more. Among them: the precise investigation into the inner senses and their function in representation, and the clarification of the way of establishing them among the philosophers and theologians, and the interpretation of the denial of some theologians of them, and the clarification of which is more fitting: to subsume them under reason or to count them as causes independently.